Is there increased risk of childhood cancers after assisted reproductive techniques? - Tuğcu, Deniz; Özhan, Nail; Ünüvar, Ayşegül; Karaman, Seyfettin Senih; Tuna, Rujnan; Bilici, Muhammed Veysel; Sönmez Şahin, Şeyma; Anak, Sema; Devecioğlu, Ömer; Öztürk, Gülyüz Hanife; Ağaoğlu, Leyla; Karakaş, Zeynep (Wiley, 2020)
[Abstract Not Available]
Keywords: Childhood Cancers; Increased Risk; Reproductive Techniques